The difference of corrosion resistance between NiTi archwires and NiTi with additional cooper archwires in artificial saliva - Eddy H. Habar; Fransiske Tatengkeng (Journal of Dentomaxillofacial Science, 2020)
Objective: The aim of this experiment showed the difference of corrosion resistance between Nickel-Titanium (NiTi) archwire and NiTi archwire with additional cooper (NiTi-Cu) in artificial saliva.Material and Methods: This research was conducted in these laboratory experiments, immersed the NiTi archwires and NiTi-Cu archwires on artificial saliva at pH= 7 and incubated on 37oC, with the ratio of the archwire and the saliva was 0.02 gr: 1 ml during 1 day, 33 days and 66 days.Results: Corrosion resistances reviewed by average saliva artificial contained ion Ni after immersed 1 day of NiTi archwires and NiTi-Cu were 0.033 ± 0.000, and after immersed 33 days were 0.053 ± 0.022 and 0.101 ± 0.050, and after 66 days immersed were 0.101 ± 0.050 and 8.052 ± 3.4667.Conclusion: Based on research conducted, NiTi archwire more resistant to corrosion than NiTi-Cu, ion Ni released shown higher concentration in NiTi-Cu than NiTi.